Creative Entrepreneurship Mindset: Comparative Study between Millennial Generation and Generation Z - Kiat, Ton; Lek, Siri; Thai, Aom (Journal of Social Entrepreneurship and Creative Technology, 2024)
The increasing prominence of creative entrepreneurship has been driven by shifts in consumer behavior, technological advancements, and changing work environments. Both the Millennial and Generation Z cohorts exhibit distinct entrepreneurial tendencies, shaped by different societal, technological, and economic contexts. However, there remains a gap in understanding how these generational differences impact the development of a creative entrepreneurship mindset. This study aims to compare the creative entrepreneurship mindset between Millennials and Generation Z, examining the factors that influence their entrepreneurial behaviors, decision-making, and approach to creative industries. A comparative research design was employed, utilizing both qualitative and quantitative methods. A total of 200 participants, 100 Millennials and 100 Generation Z individuals, were surveyed and interviewed. The survey focused on key entrepreneurial traits such as risk-taking, innovation, and adaptability, while the interviews provided deeper insights into their motivations, challenges, and perceptions regarding creative entrepreneurship. The findings indicate significant differences between the two generations in terms of risk tolerance, innovation, and digital fluency. Generation Z tends to exhibit higher levels of digital fluency and a preference for social media-driven entrepreneurship, while Millennials show more inclination towards traditional business models. Additionally, Generation Z shows a stronger preference for flexible, remote work environments, valuing autonomy and self-expression. The study concludes that while both generations demonstrate entrepreneurial potential, their approaches to creative entrepreneurship differ significantly. Understanding these differences can help educators, policymakers, and entrepreneurs develop tailored support programs to foster entrepreneurial growth in both generations.